(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The hotel industry is the largest and most rapidly growing industry in Thailand. Many tourists are travelling from many different countries around the world, the ability for hotel staffs to use multi-languages in communication with guests, such as English, Chinese and Japanese is becoming ever so needed as an absolute minimal requirement. Due to widespread difficulties with language barrier the many hotels hire the native speaker to solve this problem. This study, therefore, explored the effectiveness of human resource practices (HRP) toward awareness of intercultural communication among 5 star-rated staff. Data were collected from expatriate staffs in 5 star-rated Thai hotel chain in Thailand. A total of 578 valid questionnaires were obtained and analyzed by using structural equation modeling to test the hypothesis. The main results indicate that HRP had a positive, direct effect on the awareness of intercultural communication among 5 star-rated in Thailand. The authors provide significant HRP theoretical to advise the department of Human Resources in the hospitality industry.